2011
DOI: 10.1007/s10661-011-2327-9
|View full text |Cite
|
Sign up to set email alerts
|

Integrated approach for demarcating subsurface pollution and saline water intrusion zones in SIPCOT area: a case study from Cuddalore in Southern India

Abstract: This paper deals with a systematic hydrogeological, geophysical, and hydrochemical investigations carried out in SIPCOT area in Southern India to demarcate groundwater pollution and saline intrusion through Uppanar River, which flows parallel to sea coast with high salinity (average TDS 28, 870 mg/l) due to back waters as well as discharge of industrial and domestic effluents. Hydrogeological and geophysical investigations comprising topographic survey, self-potential, multi-electrode resistivity imaging, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…The coastline of Tamil Nadu and Pondicherry comprises a number of cusps, spits and wave-cut platforms and several palaeo-shorelines (GSI 2006 Table 2). The results from agricultural soil corroborate with the works of Sankaran et al (2012) reported from surface soil of SIPCOT. Roadside soils showed a high degree of contamination that can be attributed to motor vehicles.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The coastline of Tamil Nadu and Pondicherry comprises a number of cusps, spits and wave-cut platforms and several palaeo-shorelines (GSI 2006 Table 2). The results from agricultural soil corroborate with the works of Sankaran et al (2012) reported from surface soil of SIPCOT. Roadside soils showed a high degree of contamination that can be attributed to motor vehicles.…”
Section: Resultssupporting
confidence: 90%
“…The area is marked with high salinity due to discharge from domestic and industrial effluents. Some of closed industries of the area have continuously dumped scrap and chemicals like sulphuric acid, sulphur, lime, pesticides and other raw materials, which were the chief sources of subsurface contamination (Sankaran et al 2012). Pondicherry University ground soil was taken as relatively uncontaminated control (Fig.…”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prasanth et al (2012) examined the suitability of ground water quality for irrigation and domestic purpose in of Alappuzha District, Kerala. Sathish and Elango (2011) identified groundwater quality variation and proposed vulnerability map of the south Chennai coastal aquifer, while Sankaran et al (2012) identified groundwater pollution and saline intrusion through Uppanar River, which flows parallel to sea coast in Cuddalore. Singh and Jha (2014) researched on tide dynamics in the coastal aquifer system.…”
Section: Coastal Aquifersmentioning
confidence: 99%
“…Presentation of chemical analysis in graphical forms makes the understanding of complex groundwater system simpler and quicker. Several researchers followed a series of methods to interpret and classify the groundwater chemistry in hard rock Mondal et al 2013) as well as soft rock aquifers (Subramanian 1994;Saxena et al 2003) including coastal zones in Southern India (Mondal et al 2010, Sankaran et al 2012. Using GIS technique (Senosy and Dahab 1997;Deev et al 2012;Antony Ravindran 2013), the quality of groundwater was analyzed for systematic geochemical mapping in the irrigation purpose.…”
Section: Introductionmentioning
confidence: 99%